The song as literary text in the english language classroom: a collaborative experience in basic education - Mello, Layssa Gabriela Almeida e Silva (The ESPecialist, 2023)
This article aims to present a didactic proposal developed with a group of students from the 8th grade of elementary school, based on the song “Blowing in the wind”, by Bob Dylan. The idea lies in discussing with the aforementioned group the possibility of a song being a literary text. Therefore, pre-listening, reading/listening to the song and post-reading activities were carried out, seeking to highlight the social criticism woven by the American singer and composer and the metaphors present in it. The activities were developed collaboratively, in groups and pairs, and the data indicate that the aforementioned literary text favored the establishment of dialogical and intercultural relations between the participants and singer-songwriter Bob Dylan. I do not hope with this didactic proposal to exhaust the countless possibilities for discussion and interpretation of the song, but rather to rethink the characteristics inherent to the song genre, favoring its use as a literary text in the teaching and learning process.